Cyberchondria Amidst COVID-19 Pandemic: Challenges and Management Strategies - Varma, Rahul; Das, Sreeja; Singh, Tushar (Frontiers in Psychiatry, 2021)
The corona-virus disease 2019 (COVID-19), first found in Wuhan, China in December 2019, has posed an inexplicable threat to the global community. After its inception, the virus proliferated rapidly, which led to the cause of millions of deaths, and having a detrimental effect on physical health, social lives, economic uncertainty, and mental health of people. The World Health Organization has reported that there are 111 million confirmed cases of COVID-19 and 2.45 million deaths due to COVID-19 worldwide. Indisputably, the present pandemic has contributed to the extensive psychological and environmental distress together with clinical depression, anxiety and post-traumatic stress disorder (PTSD), domestic violence, and unemployment. Due to the ambiguous nature of the pandemic, educational organizations, and outdoor activities are closed, thus burdening the mental health of younger populations. Children as well as youths are more glued to the Internet for their studies, online gaming, shopping, watching movies, and searching health-related information. Despite the advantages of using the Internet, it has some severe consequences too. Some people are repeatedly searching for physical and mental well-being related information without verifying credible sources, which, in turn, causes distress and anxiety. In such situations, individuals may end up contributing to an illness known as cyberchondria. In this paper, we have tried to highlight the problematic use of Internet for health-related searches and have outlined the management of such illness. We suggest two strategies: firstly, to reduce repeated online searches of health information and, secondly, to manage anxiety-augmenting thoughts that are triggered due to the maladaptive thoughts caused by the abstruse information.